Assessment of the Response to Fertilization for the Sustainable Management of Native Grasses from Flooded Savannah Ecosystem Arauca, Colombian Orinoquia. (2024)
The native grasses of the flooded savannah ecosystem are produced under natural conditions and there is little information on the productive and nutritional response to the application of fertilizers. They are proposed as a strategy for adaptation to climate change and for the sustainable development of livestock farming. The aim of the study was to evaluate the response to low doses of fertilization of native grasses (“bank” grasses: Paspalum plicatulum, Panicum versicolor, and Paspalum sp. “Low” grasses: Leersia hexandra and Hymenachne amplexicaulis) in flooded savannah conditions. The green forage samples were taken in a 1 m2 frame at 28-, 35-, and 42-day cutting intervals and biomass production was estimated with and without fertilization. After 35 days, the nutritional composition was analyzed by near-infrared reflectance spectroscopy (NIRS). The effect of fertilization and the grasses × cutting interval interaction influenced (p < 0.05) green forage (GF, t/ha) and dry matter (DM, t/ha). The effect of fertilization and the grasses × fertilization interaction on the nutritional composition only influenced the content of calcium (Ca2+) and magnesium (Mg2+) in the “low” grasses, while in the “bank” grasses, it influenced the sodium (Na) content (p < 0.05). The application of fertilizers generated significant differences in forage yield, but not in the general nutritional composition of grasses. However, some numerical variations were observed in favor of fertilized grasses. According to these results, the application of fertilizers will not be required to increase the value of the nutritional composition. Native grasses constitute an important sustainable food resource for livestock in flooded savannah ecosystems. This study constitutes the first approximation to understanding the behavior of native grasses for sustainable management in the flooded savannah ecosystem.